Vertical distribution of Hymenoptera (Insecta) in pine forests of the European part of Russia - Ruchin Alexander (BIO Web of Conferences)
A study was conducted on the vertical distribution of Hymenoptera in pine forests in the central European part of Russia (Republic of Mordovia). Beer traps were used as the primary method for insect capture. Species from the Vespidae family were dominant. Vespidae exhibited the highest population density, with Vespa crabro and Vespula vulgaris being most abundant in the traps. The highest numbers of both species were recorded at a height of 1.5 meters from ground level, while significantly lower numbers were observed at 12 meters. Dolichovespula media showed relatively consistent numbers across all heights. Polistes nimpha was only observed at heights of 1.5 and 3 meters. Vespula germanica was most abundant at 12 meters, whereas Vespula rufa had the highest density at 3 meters. Seasonal population dynamics showed a minimum in June, with peaks in July and August. Population trends remained consistent across different heights.